PHILOSOPHICAL FOUNDATIONS OF ABU NASR FARABI’S VIEWS ON RELIGION - Khaidarova Larisa Sunnatovna (Bright Mind Publishing, 2025)
This article examines the philosophical foundations of Abu Nasr Farabi’s views on religion within the context of his broader metaphysical, ethical, and socio-political thought. Farabi approaches religion not merely as a system of beliefs or rituals, but as a symbolic and practical expression of philosophical truth adapted to the cognitive and moral capacities of society. The study analyzes the relationship between religion and reason, revelation and intellect, as well as religion’s role in moral education and the construction of a virtuous society. Special attention is given to Farabi’s concept of the “virtuous city” and his understanding of religious leadership, happiness, and moral perfection. The article argues that Farabi’s religious philosophy represents a rational-humanistic synthesis that remains relevant in contemporary discussions on religion, ethics, and social harmony.
Keywords: Abu Nasr Farabi, philosophy of religion, reason and revelation, virtuous city, ethics, happiness, Islamic philosophy.